Objective indicators of quality of life in people with different visual status - Stanimirov, Ksenija; Jablan, Branka; MIjatović, Luka; Grbović, Aleksandra (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Quality of life is a broad and complex construct. World Health Organization refers to it as an “individual’s perception of their position in life (…) in relation to their goals, expectations, standards, and concerns”. Reduced visual functions have a negative impact on the overall individual’s functioning. Difficulties in accessing visual information and problems in orientation and mobility create significant limitations in performing daily activities and lead to diminished opportunities for education, work, social participation, and leisure. Limited participation in the aforementioned areas with lower social interactions have a negative impact on the individual’s quality of life. However, it is unclear whether this construct of people with visual impairment is compromised due to reduced ability to perform daily activities or due to difficulties in establishing social interactions. Objectives. In an effort to indicate the consequences of visual impairment on quality of life, the goal of this research was to determine the objective quality of life in adults with different visual status when controlling the age. Methods. The Comprehensive Quality of Life Scale was used to evaluate the quality of life. The sample consisted of 175 people – 92 participants with visual impairment and 83 participants without structural or functional problems in the visual system. Results. Results of eight one-way ANCOVAs indicated a significant effect of visual status on Objective quality of life in total (p < .001) and on its four domains: Material well-being, Health, Productivity, Place in Community. Conclusion. The effects of different visual status on the observed construct revealed when age as a variable is controlled.
Keywords: objective quality of life; visual status; visual impairment; adults